A Juridical Study toward Indonesian Disabilities Right for Public Services Accessibility according to Law No. 8 Year 2016 - Jefri Tamba (The Center for Disability Studies and Services Brawijaya University, 2017)
In this study, the author is very attentive to law for disability. In 2016, the Indonesian government has been launched a recovering law for persons with disabilities, namely Law No. 8 Year 2016. Differ with the previous law, Law No. 4 Year 1997 which still less contains the rights of persons with disabilities, especially on the things of public services accessibility. Hence, regarding to the normative analysis toward Law No. 8 Year 2016 which is used in this study. It found that the Indonesian government is already loaded the persons with disabilities right on public services accessibility. Those listed in Chapter III, Part 15 article 19 on Public Service Rights. Therefore, the development of public service facility for persons with disabilities shall be appropriate to this law. Furthermore, the details of public service in terms of implementation of respect, protection and rights meeting with disabilities are initiated by both central and local governments. All public services in Indonesia should be take attention to the Law No. 8 Year 2016 on Persons with Disabilities.